Interactivity of WebGIS for the Simulation of Land Development - Di Giacomo, Tullia Valeria (TeMA - Journal of Land Use, Mobility and Environment, 2015)
In the definition of scenarios as key components underlying the decisions on city’s and territory’s transformation processes stands the comprehension of the interactions between multiple aspects that influence that dynamics. The spatial data knowledge and the development of new ICT solutions which can guide the planner towards strategic, reliable and shared decisions are essential. It is proposed a methodology in which to specialize the special approach established in previous projects developed by extending and implementing GIS technology Geographic Information System towards online interoperability. The control of the effects of changes in land use in environmental quality, particularly in the water resources management, can thus become operational in the network through the application of innovative tools able to meet the new challenges of urban regeneration.